Strategies for Working with Families: Guiding families through stressfull events - Bader, Edward (1991)
Family physicians are in contact with families as they pass through various stages and become aware of marital and family problems. By offering guidance and patient education before problems arise, physicians can avoid trouble and encourage healthy marital and parenting patterns. This article presents the Family Life Cycle framework and discusses the stresses that occur at marriage and at the birth of the first child. Helpful tools can be shared with patients.